KEEFEKTIFAN METODE DEMONSTRASI BERBANTU MEDIA KAPAS TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS II SD NEGERI SAMBIREJO 01 SEMARANG - Iin Purnama Sari; Satria Maulana (Universitas PGRI Semarang, 2013)
Second grade students of SD Negeri 01 Semarang Sambirejo still having trouble in learning mathematics, especially in understanding the material operations of multiplication count numbers. Mathematics is one of the important subjects. So with these circumstances, it is necessary to do the learning that can improve student learning outcomes. One is to apply the method of demonstration KAPAS media assisted in learning. Formulation of the problem is revealed in this study is whether the application of the method demonstration assisted KAPAS media effectively improve student learning outcomes Math class II SD Negeri 01 Semarang Sambirejo? Goals to be achieved in this research is to determine whether the application of methods of assisted demonstration KAPAS media effectively improve student learning outcomes Math class II SD Negeri 01 Semarang Sambirejo. This type of research is experimental research. The study design used was a Posttest-only Control Design. Population in this research that all students in elementary school Sambirejo 01 Semarang, amounting to 406 students and the sample used is grade II for a total of 75 students were divided into two classes, totaling 36 students IIA and IIB class numbered 39 students. The study is a sampling Probability sampling, cluster sampling technique with random sampling. Data analysis techniques in this study using a preliminary analysis using the normality test and test the equality of two on average, for final analysis using normality test, mastery learning and test two sides (t-test). Based on the analysis of research data after getting treatment showed that the learning outcomes Math class achieve mastery learning experiment, judging from the list of the test (test mastery learning) with derived table = 1.684 and t = 8.271. It means that the average passing grade experimental class is not the same as 72, and of the t-test results obtained coefficient = 2.554 and t table = 1.995, for t> t table then Ho is rejected, so it can be concluded that the application of methods of assisted demonstration KAPAS media effectively increase student learning outcomes Math II class 01 SD Negeri Semarang Sambirejo academic year 2012/2013. Suggestions to make is that this study can be applied by teachers in school as activities of innovation and creativity in implementing the learning aims to improve student learning outcomes.